Profesionalisme Guru Pendidikan Agama Kristen Pada Tingkat Sekolah Menengah Atas di Kota Manado Tahun 2018 (Pascasarjana IAKN Manado, 2020)
This article examines the professionalism of Christian Religious Education Teachers at the Senior High School level in Manado City. The research was conducted using qualitative methods which were built from literature research, observation and interviews. This study begins with research on the professionalism of teachers, both teachers in general and Christian Religious Education teachers which are based on the example of the life and ministry of the Lord Jesus Christ as the Great Teacher. Then proceed with empirical research on the form of professionalism of Christian Religious Education teachers, the obstacles faced by Christian Religious Education teachers in increasing their professionalism and the efforts of Christian Religious Education teachers in overcoming obstacles to increase their professionalism. The results of the study show that there is an opinion regarding professional teachers of Christian Religious Education at the high school level in the city of Manado which have links to formalities such as a minimum bachelor's diploma, following the teacher certification process, education and training, understanding the curriculum and alliances with fellow teachers. The obstacle for a Christian Religious Education teacher in increasing his professionalism comes from external factors such as the limited development costs and opportunities for developing Christian Religious Education teachers themselves. Meanwhile, the efforts of a Christian Religious Education teacher in overcoming obstacles in increasing professionalism are also external factors such as further studies, mastery of the curriculum and skills in the preparation of learning tools. With the results of this study, it is possible to recommend proposals for Christian Religious Education teachers, especially in the city of Manado for the professional development of teachers using the Action Research model. This model provides opportunities for Christian Religious Education teachers to be involved and as the main actors in the learning process, they identify and find problems, and then explore, explore and find their own answers to problems they encounter in the field. The Action Research Model is a model that can be an alternative choice to help teachers develop their professionalism.